Uganda : Technical Assistance Report-Moving Towards Risk-Based Supervision of Insurance in Uganda: Training on Supervision of Reinsurance and Assisting on an Industry Seminar on Risk-Based Supervision. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the recommendations made by the IMF mission to assist Uganda in moving toward risk-based supervision of insurance sector. It highlights that under the revised insurance legislation, the Insurance Regulatory Authority of Uganda (IRA) will be requiring nonlife insurers to provide certification for adequacy of technical provisions by an actuary as is currently required for life insurers. When the requirement comes into effect, it will be necessary for it to be supported by guidance from IRA in terms of its expectations for the actuarial reports to be filed. This will ensure consistency in reporting to the IRA and that the reports will provide the information needed by the IRA for supervisory purposes.